Prevention of white impurities in vaname shrimp (Litopenaeus vannamei) using noni fruit extract (Morinda citrifolia) in semi-intensive shrimp cultivation system - Farastuti, Eko Rini; Mumpuni FS ,; Mulyana,; Faizi AL,; Taufik M,; Hamdani FI, (JURNAL MINA SAINS, 2023)
White vanamae shrimp is one of the superior commodities in aquaculture. Currently, the productivity of white vanamae shrimp has not yet reached its production target. So, it is necessary to increase the amount of production on a gradual scale carried out by the community. In shrimp farming activities, disease problems are often encountered. Namely is a white stool, white feces, or White Feces Disease (WFD). The clinical symptoms that arise when shrimp are attacked by White Feces Disease (WFD) are that the shrimp's appetite decreases, the shrimp's intestines change color to white and even look empty due to lack of food intake, white feces floating on the surface of the water, and the shrimp's growth becomes abnormal. This WFD disease can be caused by poor cultivation practices, unhealthy seeds, and poor water quality, causing the emergence of disease microorganisms such as Vibrio sp bacteria. One way to treat this disease is to provide alternative medicine, noni fruit extract. This research consisted of 3 noni extract treatments and consisted of 3 replications, namely Treatment A: 10 mL/L; Treatment B: 15 mL/L; Treatment C: 20 mL/L. The noni dose is given at the specified dose once daily for one month. The survival rate of shrimp increased to 86.7%.